Web-based Counseling System (WBCS) / Woo Swee Hong - Woo, Swee Hong (2002)
Web-based Counseling System (WBCS) is a web-based system developed with objectives of implementing the system in the Internet as a solution to provide counseling services to those who needs. The system allows the authorized users to use all the service that the system provides. In this new millennium , computer and Internet have proved that they are an important part of human's life. No doubt, without Internet and computers, human's life will be a chaos. So, this project is developed to suit the changes of the world. This Web-based Counseling System is a combination of web-based system and client server application system. The clients will be any desktop computers link to the server. Whenever the clients want to retrieve information from the system, it just pass are request to the server and get the reply from the server. The server side contains all the related HTML pages, database and rules. The server will also processes the request from the client and then sends the result back to the clients. The Web-based Counseling System can be divided into two sections:user and administration. The user section allows users browse through all the services that the system provides like search, chat room, forum analysis and feed back. The administration section provides an application for the administrator to update the counseling information in the database, view user profile, view feedback and post important news to the users. With so many people sitting in front of a computer and accessing to the World Wide Web, Web-based Counseling System will be an alternative choice for them to visit. They can share their experience with the other users and this will really help those who need the suggestions. Although the system cannot read the non-verbal actions from the counselees, but it helps those who are shamed to discuss their problem with other people